A precast wall connector - Hejazi, Farzad; Mohd Saleh, Jaafar; Abang Ali, Abang Adbullah; Vaghei, Ramin (2014)
The present invention relates to a precast wall connector comprising: a male steel channel unit (100) attached at first concrete part; a female steel channel unit (200) attached at second concrete part; bolt and nut (300) to brace the male steel channel unit (100) interlocking to the female steel channel unit (200); characterized in that the interlocking of the male steel channel unit (100) to the female steel channel unit (200) which having a rubber channel (207) sandwiched in between enables the concretes to withstand multidirectional dynamic load against the concretes. The above provisions are advantageous as the present inventions enables the concretes to withstand dynamic loads, regardless the direction of the force is exerted against the concrete. The present invention also applicable for various joint positions, reduces time to assembly, provides no dependency on skilled labours and speeds up construction process.